(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2023)
The article presents the ERC research project DEMALPS, which studies late medieval mountain areas as the cradle of radically new political experiences, inspired by original values and practices of self-governance. The focus of the project is on the fourteenth- and fifteenth-century Western Alps, a broad territory (including modern French, Italian and Swiss regions) which saw unprecedented political unrest and experimentation with forms and institutions. Based on a rich corpus of sources, mostly scattered across local municipal archives, DEMALPS will offer an extraordinary insight into the Alpine inhabitants’ political ideals and connections, which will be explored through an interdisciplinary approach combining medieval history, digital humanities, diplomatics, and archival science. DEMALPS proposes to be a native digital project specifically designed for collaborative work, thanks to the development of an online application to collect, analyse and share data within the team and subsequently with the scholarly community.